Cultivo de cártamo (Cartamos tinctorius L.) sob variação de adubações, densidades e épocas de plantio - Sampaio, Marinez Carpiski (2016)
The field studies were done in the city of Cascavel, PR, during the planting season in fall and winter in 2014 as planting seasons. This study aimed to determine the effect of fertilizer doses and plant density variation in the row in two seasons safflower crop cultivation in the production of component, grain yield and oil content. The experimental design was a randomized block design with three replications. Each block was divided into five plots with four different planting densities (5, 10, 15 and 20 plants per linear meter), where different doses of NPK were applied (0, 200, 400, 600 and 800 kg ha-1) in the composition 4 14 8. Plant samples were evaluated for the verification of phenological data of number of branches, fresh and dry branch, number of capsules, fresh and dry capsules, plant height, stem diameter, stem length, fresh and dry stem, fresh and dry root and the end of the season productivity (kg ha-1), 1000 grain weight and seed oil content. Data were subjected to analysis of variance (ANOVA) test regression and response surface at 5% probability using the Genes software. According to the data analyzed, the growing season did not influence the number of branches and seed oil content. The plant density did not affect the plant height and the weight of 1000 grains and fertilizer doses did not affect the number of branches, plant height, stem fresh weight, yield, 1000-grain weight and oil content. The results obtained for the final yield of safflower crop were the first growing season (autumn) associated with higher plant density (20 pl./m. linear), aggregates the largest fertilizer dose (800 kg ha-1) , with these conditions, the most suitable for safflower cultivation in the region of the study